2004
DOI: 10.1111/j.1601-5223.1996.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Localization of 5S rRNA Genes in the Pig by Fluorescence in Situ Hybridization

Abstract: Ribosomal RNA genes (rRNA genes or rDNA) in higher eukaryotes are organized into two distinct gene classes. One class comprises the genes encoding 18S, 5.8S, and 28s ribosomal RNA. These genes are arranged as tandemly repeated clusters that are localized at specialized sites on the chromosomes known as nucleolar organizer regions (NORs). The other rDNA class, 5s rDNA, is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In man and in American mink 5S rRNA genes are organised in more than one cluster (Kost et al, 1995;Lomholt et al, 1995a;Christensen et al, 1998) while in the mouse, the rat and in the pig only one cluster was detected (Matsuda et al, 1994;Lomholt et al, 1995b;Mellink et al, 1996;Suzuki et al, 1996). The present study revealed the existence of a single 5S rRNA gene cluster for the maned wolf (proximal on 5q3), for the bat-eared fox (proximal on chromosome 19q5) and the fennec fox (distal on chromosome 12q6).…”
Section: Discussionmentioning
confidence: 62%
“…In man and in American mink 5S rRNA genes are organised in more than one cluster (Kost et al, 1995;Lomholt et al, 1995a;Christensen et al, 1998) while in the mouse, the rat and in the pig only one cluster was detected (Matsuda et al, 1994;Lomholt et al, 1995b;Mellink et al, 1996;Suzuki et al, 1996). The present study revealed the existence of a single 5S rRNA gene cluster for the maned wolf (proximal on 5q3), for the bat-eared fox (proximal on chromosome 19q5) and the fennec fox (distal on chromosome 12q6).…”
Section: Discussionmentioning
confidence: 62%
“…In almost all the fish species studied, the location of the 5S rDNA occurs at an interstitial position in the chromosomes. This same 5S rDNA chromosomal location has been observed in mammals (Mellink et al, 1996;Frederiksen et al, 1997;Mäkinem et al, 1997; among others) and amphibians (Vitelli et al, 1982;Schmid et al, 1987;Lucchini et al, 1993), suggesting that such organization may not be casual. An interstitial distribution for the 5S rRNA gene loci could represent some advantage related to the organization of these genes in the vertebrate genome (Martins and Galetti, 2001b).…”
Section: Chromosome Locationmentioning
confidence: 52%
“…Although the chromosome structure of the 5S rDNA clusters of these families seems to have been preserved from major changes during evolution, their nucleotide sequence seems to be evolving fast. Martins and Wasko (2004) have pointed out that in piscines the 5S rDNA repeat clusters are most commonly located at interstitial chromosome sites, and this has also been reported for mammals (Mellink et al, 1996;Frederiksen et al, 1997;Mäkinem et al, 1997) and amphibians (Vitelli et al, 1982;Schmid et al, 1987;Lucchini et al, 1993), suggesting that such distribution could represent some advantage related to the organization of these genes in the vertebrate genome (Martins and Galetti, 1999). It is interesting to note that even in other piscine species with high rates of chromosome variations such as the genus Astyanax (Characidae), the 5S rDNA chromosome clusters are conserved among species (Almeida-Toledo et al, 2002;Mantovani et al, 2005).…”
Section: Resultsmentioning
confidence: 86%